The Impact of Brand Experience on Brand Engagement with Meditating Role of Brand Love and Brand Trust - Valikchali, Morteza Asghari (International Journal of Applied Research in Management and Economics, 2022)
The present study aims to investigate the impact of brand experience on brand engagement with mediating role of brand love and brand trust. Within the literature, there have been a select few studies that have focused on these factors in case of Bank Melli Iran. To this end, a case study approach was utilized in which 384 customers of Bank Melli Iran in Sari (both male and female) were selected based on available non-random sampling method and the formula of Cochran to participate in this study. Data collection method was library and field type. In the field method, we used the standard questionnaire. To evaluate the validity while using content validity, structural validity (convergent, divergent validity and composite reliability) was also used. The reliability of the questionnaire was assessed by Cronbach's alpha test. The results of convergent, divergent and composite reliability studies showed a good fit of measurement models, and also the results of Cronbach's alpha study showed a good reliability of each variable. After ensuring the validity and reliability of the research questionnaire, the final data collection was performed and the results were analyzed using structural equation modeling under partial least squares (PLS). Finally, the results showed that brand experience, both directly and indirectly, mediated by brand love and brand trust, has a positive effect on brand engagement.